Presentation mining tool: from slides to mind maps - Kasinathan, Vinothini; Mustapha, Aida; Azmi Murad, Masrah Azrifah; O. K. Rahmat, Rahmita Wirza; Mansor, Evi Indriasari (International Information Institute, 2016)
Slide presentations such as the PowerPoint presents knowledge by the subject matter expert in a linear sequence. Nonetheless, post-presentation, the knowledge is actually reconstructed differently by the learners depending on their personal understanding over the entire presentation. To enhance learning, this paper presents a presentation mining tool that is able to extract keywords and key phrases from a collection of Microsoft PowerPoint slides and generate a mind map with topics and subtopics based on the extracted keywords. The mind map produced by the system contains the main topic as the central node of the map with branches connecting main topic to subtopics. The mind map produced through automatic extraction of topic and subtopics is aimed to help learners to concentrate on the entire concept rather than following through the slides sequentially.